MARRIAGE MANAGEMENT INFORMATION SYSTEM IN IMPROVING THE QUALITY OF SERVICES AT THE OFFICE OF RELIGIOUS AFFAIRS - Lailatul Qadariyah; Andi Haerudin; Uslan Adinata (Sekolah TInggi Ilmu Dakwa dan Komunikasi Islam (STIDKIS) Al Mardliyyah Pamekasa, 2025)
The Marriage Management Information System is capable of making administrative marriage services at the Cengkareng Sub-District Office of Religious Affairs more modern, faster, and reliable in efforts to improve the quality of services to the public, particularly marriage services. This study aims to examine service communication through the Marriage Management Information System as well as understanding of the system and the services available within it. The study employs a descriptive qualitative approach with data collection through observation, interviews, and document studies. The research subjects include the head of the Office of Religious Affairs, staff members, and prospective brides and grooms. Service communication through the Marriage Management Information System improves the quality of services at the Cengkareng Office of Religious Affairs through several aspects, namely the implementation of administrative marriage services, the impact of the system on service speed and reliability, and communication strategies in the socialization of the system from the perspective of Islamic Broadcasting Communication. Solutions for enhancing socialization include the use of social media, brochures, and religious forums. In addition, improving internet network capacity, intensive training for system officers, and attention to public complaints are key to minimizing technical obstacles. This ensures that the public can easily use the system and that services become more effective and efficient. In conclusion, the Marriage Management Information System has proven to improve the quality of marriage services at the Cengkareng Office of Religious Affairs through effective communication and utilization of digital technology.